(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2000)
Noriaster barberoi gen. et. sp. n. is based on a single specimen from the Calcare di Zorzino (Norian, Triassic) of northern Italy. A member of the surviving Poraniidae (Valvatida; Echinodermata), N. barberoi is the oldest-known species assignable to a Jurassic and younger family and the first such species known from the Triassic. No Paleozoic species with close affinities with crown-group families has been recognized. Noriaster and the slightly older Triassic genus Trichasteropsis from the Muschelkalk of Germany together indicate that the diversification of crown-group asteroids was well underway at least by Middle and Late Triassic time. Phylogeny of crown-group asteroids is problematic because extant familial-level taxa are morphologically divergent, and they exhibit comparatively few uncontested characters that clearly indicate phylogenetic affinities and sequence. Familial assignment of Noriaster is supported by a new cladistic analysis. To the student of living asteroids, the appearance of a living Noriaster would be remarkable only because it would seem so commonplace. To the extent that form correlates with function, Noriaster suggests that modern asteroid life modes emerged quite promptly during the Mesozoic asteroid diversification.